A three-phase current source inverter with third harmonic injection for grid-connected renewable power sources - Ninković Predrag; Janda Žarko; Pejović Predrag (Zbornik Radova: Elektrotehnički Institut "Nikola Tesla")
A novel three-phase voltage-synchronized current source (VSCS) converter with third harmonic injection is proposed in this paper. Compared with the conventional vector current control (VCC), phaselocked loop (PLL) is completely removed in this method. This new type of current-source inverters is suitable for application in grid-connected renewable power sources. It is based on a three-phase six-pulse inverter topology with unidirectional switches using line-synchronous control to achieve unity displacement factor at the point of common connection. An additional power circuit to implement the third-harmonic current injection technique is used in order to improve the line current total harmonic distortion. The proposed approach ensures stable operation under weak grid conditions. Experimental results on a 1.5 kW prototype with the optimal third harmonic current injection are shown. The theoretical predictions of total harmonic distortion and power factor improvement are confirmed experimentally.